Perceived inclusivity and trust in protected area management decisions among stakeholders in Alaska. Issue 3 (11th March 2022) - Goodson, Devin J.; van Riper, Carena J.; Andrade, Riley; Cebrián‐Piqueras, Miguel A.; Hauber, Mark E.
Abstract: The success of conservation initiatives often depends on the inclusion of diverse stakeholder interests in the decision‐making process. Yet, there is a paucity of empirical knowledge concerning the factors that explain why stakeholders do—or do not— believe that they are meaningfully represented by government agencies. Our study provides insight into the relationship between trust and stakeholder perceptions of inclusivity in public land management decisions. Here, we focus on the U.S. state of Alaska, where almost two‐thirds of the land area are managed by the federal government. We used structural equation modelling to test whether an individual's trust and the information sources used to learn about land management positively influenced perceived inclusivity. We conceptualized trust in terms of four dimensions that reflected an individual's disposition to trust, trust in the federal government, trust in shared values and trust that agencies adhere to a moral code. We found that survey respondents across the U.S. state of Alaska had a limited disposition to trust others, did not trust federal land management agencies, did not believe agencies shared their values pertaining to protected area management and did not believe that agencies adhered to a moral code. Beliefs about the morality of agencies were the primary driver of perceived inclusivity in land management decisions, indicating that agencies should focus on solving problems through deliberation and discussion about moral principles rather than by force. Information acquired from professional, community‐based or environmental advocacy exchanges also positively influenced perceived levels of involvement among stakeholders in resource management decisions. These results provide a roadmap for how land management agencies can improve public relations and work towards a model of inclusive conservation around protected areas. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: El éxito de las iniciativas de conservación depende a menudo de la inclusión de los diversos intereses de las partes interesadas en el proceso de toma de decisiones. Sin embargo, son escasos los conocimientos empíricos sobre los factores que explican por qué las partes interesadas creen ‐o no‐ que estén significativamente representadas por los organismos gubernamentales. Nuestro estudio permite conocer la relación entre la confianza y la percepción de inclusión de las partes interesadas en las decisiones de gestión del suelo público. En este caso, nos centramos en el estado de Alaska, donde casi dos tercios de la superficie terrestre está gestionada por el gobierno federal. Utilizamos un modelo de ecuaciones estructurales para comprobar si la confianza de un individuo y las fuentes de información utilizadas para aprender sobre la gestión del territorio influyeron positivamente en la percepción de la inclusividad. Conceptualizamos la confianza en términos de cuatro dimensiones que reflejaban la disposición del individuo a confiar, la confianza en el gobierno federal, la confianza en los valores compartidos y la confianza en que las instituciones se adhieran a un código moral. Descubrimos que los encuestados de todo el estado de Alaska tenían una disposición limitada a confiar en los demás, no confiaban en las instituciones federales de gestión del territorio, no creían que las instituciones compartieran sus valores relativos a la gestión de las áreas protegidas y no creían que las instituciones se adhirieran a un código moral. Las creencias sobre la moralidad de las instituciones fueron el principal motor de la inclusión percibida en las decisiones de gestión del territorio, lo que indica que las instituciones deberían centrarse en resolver los problemas mediante la deliberación y el debate sobre los principios morales en lugar de por la fuerza. La información adquirida a través de intercambios profesionales, comunitarios o de defensa del medio ambiente también influyó positivamente en los niveles percibidos de participación de las partes interesadas en las decisiones de gestión de los recursos.